ΓH2AX and p53 responses in TK6 cells discriminate promutagens and nongenotoxicants in the presence of rat liver S9. (1st July 2016) - Bernacki, Derek T.; Bryce, Steven M.; Bemis, Jeffrey C.; Kirkland, David; Dertinger, Stephen D.
Abstract : Previous work with a diverse set of reference chemicals suggests that an in vitro multiplexed flow cytometry‐based assay (MultiFlow™ DNA Damage Kit—p53, γH2AX, Phospho‐Histone H3) can distinguish direct‐acting clastogens and aneugens from nongenotoxicants (Bryce SM et al. [2016 ]: Environ Mol Mutagen 57:171‐189). This work extends this line of investigation to include compounds that require metabolic activation to form reactive electrophiles. For these experiments, TK6 cells were exposed to 11 promutagens and 37 presumed nongenotoxicants in 96 well plates. Unless precipitation or foreknowledge about cytotoxicity suggested otherwise, the highest concentration was 1 mM. Exposure occurred for 4 hr after which time cells were washed to remove S9 and test article. Immediately following the wash and again at 24 hr, cell aliquots were added to wells of a microtiter plate containing the working detergent/stain/antibody cocktail. After a brief incubation, robotic sampling was employed for walk‐away flow cytometric data acquisition. Univariate logistic regression analyses indicated that γH2AX induction and p53 activation provide the greatest degree of discrimination between clastogens and nongenotoxicants. Multivariate prediction algorithms that incorporated both of these endpoints, in each combination of time points, were evaluated. The best performing models correctly predicted 9 clastogens out of 11 and 36 nongenotoxicants out of 37. These results are encouraging as they suggest that an efficient and highly scalable multiplexed assay can effectively identify clastogenic chemicals that require bioactivation. More work is planned with a broader range of chemicals, additional cell lines, and other laboratories to further evaluate the merits and limitations of this approach. Environ. Mol. Mutagen. 57:546–558, 2016. © 2016 Wiley Periodicals, Inc.